Wetland projects developed in Brazil - Salati, E.; Salati, Eneida (IWA Publishing, 1999)
The first studies with constructed wetlands undertaken in Brazil were the result of observations made from the Amazon flood plains. The first attempt to use this capacity to change the quality of the water, in the sense of purification performed in Brazil using constructed wetland systems, was made by Salati et al. After that, new technologies were developed in a focused attempt to increase the efficiency of the system and reduce investments. Over these 18 years, persuading the Brazilian scientific community as well as the environmental control agencies to give due attention to this kind of research has required endless efforts. Only in recent years have major institutions responsible for sewage treatment and potable water supply been concerned with this type of technology for solving real problems. These institutions are as follows: SABESP (Basic Sanitation Company of Sao Paulo State), SANEPAR (Sanitation Company of Parana State) and CESP (Electric Company of Sao Paulo State). One of the private institutions that has systematically worked in the design and projects of constructed wetlands is the Institute of Applied Ecology. This institution has enhanced and developed a water depuration system based on the purifying capacity of the soil. The wetlands with filtering soils are systems formed by overlapping layers of crushed stone, gravel and soil planted with rice. This technology has been used in sewage treatment and also in water supply systems.

The first studies with constructed wetlands undertaken in Brazil were the result of observations made from the Amazon flood plains. The first attempt to use this capacity to change the quality of the water, in the sense of purification performed in Brazil using constructed wetland systems, was made by Salati et al. (1982). After that, new technologies were developed in a focused attempt to increase the efficiency of the system and reduce investments. Over these 18 years, persuading the Brazilian scientific community as well as the environmental control agencies to give due attention to this kind of research has required endless efforts. Only in recent years have major institutions responsible for sewage treatment and potable water supply been concerned with this type of technology for solving real problems. These institutions are as follows: SABESP (Basic Sanitation Company of Sao Paulo State), SANEPAR (Sanitation Company of Parana State) and CESP (Electric Company of Sao Paulo State). One of the private institutions that has systematically worked in the design and projects of constructed wetlands is the Institute of Applied Ecology. This institution has enhanced and developed a water depuration system based on the purifying capacity of the soil. The wetlands with filtering soils are systems formed by overlapping layers of crushed stone, gravel and soil planted with rice. This technology has been used in sewage treatment and also in water supply systems.
Keywords: Aquatic plants; Constructed wetland; Filtering soil; Rice production; Wastewater; Water purification; Developing countries; Plants (botany); Potable water; Sewage treatment; Societies and institutions; Wastewater treatment; Water filtration; Water pollution control; Water quality; Water supply systems; Constructed wetlands; Wetlands; drinking water; sanitation; water supply; water treatment; wetland; Brazil; conference paper; sewage treatment; technology; water management; water quality